2019
DOI: 10.1029/2018gl081302
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Cloud and Circulation Changes in Simulated Tropical Cyclones

Abstract: Observations of the diurnal cycle in tropical cyclones (TCs) systematically indicate a ∼12‐hr offset between peak rainfall rate and the maximum height of anvil clouds in the TC cloud canopy. This phasing conflicts with archetypal models of organized deep convection, which suggest a tight coupling between rainfall, vertical cloud growth, and anvil clouds. We show that this phasing owes to the bimodal diurnal evolution of the transverse circulation, which peaks nocturnally from low–midlevels, and during daytime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 49 publications
9
44
0
Order By: Relevance
“…Due to their ring-like nature, one of the Dunion et al (2014) hypotheses for diurnal pulse propagation was that they might be governed by gravity waves dynamics, perhaps initiated from enhanced deep convection in the inner core. A gravity wave interpretation of diurnal pulses has also been suggested in recent research (Navarro et al 2017;O'Neill et al 2017;Ruppert and O'Neill 2019;Evans and Nolan 2019), with calculated gravity wave phase speeds similar to the diurnal pulse propagation speed of 5-10 m s 21 found in Dunion et al (2014) and 8-14 m s 21 found in Ditchek et al (2019). Fig.…”
Section: ) Propagation Speedsupporting
confidence: 74%
“…Due to their ring-like nature, one of the Dunion et al (2014) hypotheses for diurnal pulse propagation was that they might be governed by gravity waves dynamics, perhaps initiated from enhanced deep convection in the inner core. A gravity wave interpretation of diurnal pulses has also been suggested in recent research (Navarro et al 2017;O'Neill et al 2017;Ruppert and O'Neill 2019;Evans and Nolan 2019), with calculated gravity wave phase speeds similar to the diurnal pulse propagation speed of 5-10 m s 21 found in Dunion et al (2014) and 8-14 m s 21 found in Ditchek et al (2019). Fig.…”
Section: ) Propagation Speedsupporting
confidence: 74%
“…The findings of this study support both of these hypotheses and emphasize that the upward motion in organized tropical deep convective systems is characterized by a bimodal diurnal cycle upward motion peaks nocturnally in the lower-midtroposphere and peaks in the afternoon in the upper troposphere. Such an evolution manifests in the ITCZ (Ciesielski et al, 2018), mesoscale convective clusters (Ruppert & Hohenegger, 2018), and tropical cyclones (Navarro & Hakim, 2016;Ruppert & O'Neill, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of a 10 year data set of stormcentered infrared satellite images suggested that the TC diurnal cycle may be tied to hurricane dynamics, structure and intensity change (Dunion et al, 2014). Numerical studies have also confirmed the diurnal cycle of TC structure at both the genesis (Melhauser & Zhang, 2014) and mature stages (Ruppert & O'Neill, 2019;Tang & Zhang, 2016) with attention to how radiation affects the structure and diurnal cycle of TCs. O'Neill et al (2017) investigated the possible mechanisms that are responsible for the diurnal pulsing of clouds near the TC outflow layer and found diurnal waves that have characteristics of internal gravity waves forced by heating in the TC inner core.…”
Section: Introductionmentioning
confidence: 93%